2012
DOI: 10.1016/j.pain.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations between daily chronic pain intensity, daily anger expression, and trait anger expressiveness: An ecological momentary assessment study

Abstract: Links between elevated trait anger expressiveness (anger-out) and greater chronic pain intensity are well documented, but pain-related effects of expressive behaviors actually used to regulate anger when it is experienced have been little explored. This study used ecological momentary assessment methods to explore prospective associations between daily behavioral anger expression and daily chronic pain intensity. Forty-eight chronic low back pain (LBP) patients and 36 healthy controls completed electronic diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 55 publications
3
34
3
Order By: Relevance
“…Regarding the regulation of anger, present findings are consistent with those of Bruehl et al (2012) in that lagged analyses in the present study revealed that increases in patient behavioral anger expression (above their own mean) were related to increases in pain intensity three hours later. Extending previous work, we also show for the first time that behavioral anger expression was related to increases in interference due to pain and downtime three hours later.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the regulation of anger, present findings are consistent with those of Bruehl et al (2012) in that lagged analyses in the present study revealed that increases in patient behavioral anger expression (above their own mean) were related to increases in pain intensity three hours later. Extending previous work, we also show for the first time that behavioral anger expression was related to increases in interference due to pain and downtime three hours later.…”
Section: Discussionsupporting
confidence: 91%
“…High trait anger-out people may exhibit even greater pain sensitivity when angered prior to pain-induction because of enhanced pain perception associated with simultaneous experience of strong negative affect (anger) in the absence of effective compensatory opioidergic pain modulation. These laboratory effects are supported by results from an ecological momentary assessment diary study of chronic pain patients (Bruehl, Liu, Burns, Chont, & Jamison, 2012). Here, increased momentary behavioral anger expression when the person was angered appeared to predict increased chronic pain intensity in the subsequent 4 h period.…”
Section: Introductionmentioning
confidence: 77%
“…Anger arousal may magnify subsequent pain sensitivity among individuals high in anger-out due to pain enhancing perceptual effects of anger without adequate compensatory endogenous opioid inhibitory function (Bruehl et al, 2012; Burns et al, 2004). Alternatively, anger arousal may trigger opioid release selectively among high anger-out people (Burns et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of such may be genetic, 9,69 or may be related to conditioning through prior life experience. 123 Recent work has revealed that a perception of being the victim of injustice 102,103 or anger management/expression style 12,16 is associated with the experience and/or expression of pain and disability that can be included at this stage. The parallel pathway indicating possible involvement of the central nervous system comes from emerging evidence that WAD shares many clinical and lab-based characteristics with either mild traumatic brain injury 28 or subclinical damage to spinal white matter tracts 32,93 in at least a discrete number of patients.…”
Section: Integration Of Recent and Emerging Evidencementioning
confidence: 99%